Methicillin-resistant Staphylococcus aureus strains isolated from human and environmental surfaces in a research laboratory - Eden, Vitalis Ronald; Dioso, Regidor III Poblete; Haresh, K. K.; Nishibuchi, Mitsuaki; Mahmud @ Ab Rashid, Nor Khaizura; Radu, Son (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2016)
This study aimed to investigate the susceptibility pattern of Staphylococcus aureus isolated from human and environmental surfaces in a research laboratory. A total of 320 samples from nostril (n=80), hand (n=80), door knob (n=80) and table surface (n=80) were collected for 16 weeks, before and after work. A total number of 256 samples were found positive for Staphylococcus aureus. Out of 80 randomly selected isolates, 50 (62.5%) isolates were resistant to methicillin (MRSA). Hence, the precautionary measures should be taken on self and environmental hygiene as MRSA may be transferred from humans and environmental surfaces.